Chiral Bis(imidazolidine)iodobenzene (I-Bidine) Organocatalyst for Thiochromane Synthesis Using an Asymmetric Michael/Henry Reaction - Arai, Takayoshi; Suzuki, Takumi; Inoue, Takahiro; Kuwano, Satoru (Synlett, 2017)
Bis(imidazolidine)iodobenzene (I-Bidine) was designed as an organocatalyst based on previously reported imidazolidine- or oxazolidine-containing chiral metal catalysts. I-Bidine showed catalytic activity for the Michael/Henry reaction of thiosalicyl aldehydes with nitroalkenes to give optically active thiochromanes with moderate enantiomeric excesses.
Keywords: organocatalyst; thiochromane; tandem reaction; asymmetric synthesis